2022
DOI: 10.3390/ma15062003
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Electrolytic Oxidation of Zr-1%Nb Alloy: Effect of Sodium Silicate and Boric Acid Addition to Calcium Acetate-Based Electrolyte

Abstract: This work aimed at the development of wear and corrosion resistant oxide coatings for medical implants made of zirconium alloy, by plasma electrolytic oxidation (PEO). The effect of sodium silicate and boric acid addition to calcium acetate electrolyte on the coating properties was studied. Different aspects of the PEO coating were investigated: microstructure, electrochemical and wear behavior, wettability and apatite-forming ability. The resultant coatings consist of a dense inner layer 1.4–2.2 µm thick and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Based on the XRD analysis, the surface layer of samples after PENC contains mainly iron oxides Fe3O4, Fe2O3, and FeO (Figure 27a-e), which is typical for this kind of processing [3,7,10,11]. It has been shown that, with an increase in the PENC temperature, the relative amount of oxide Fe3O4 decreases, while FeO increases.…”
Section: Phase Composition Of the Nitrocarburized Surfacementioning
confidence: 88%
See 2 more Smart Citations
“…Based on the XRD analysis, the surface layer of samples after PENC contains mainly iron oxides Fe3O4, Fe2O3, and FeO (Figure 27a-e), which is typical for this kind of processing [3,7,10,11]. It has been shown that, with an increase in the PENC temperature, the relative amount of oxide Fe3O4 decreases, while FeO increases.…”
Section: Phase Composition Of the Nitrocarburized Surfacementioning
confidence: 88%
“…Thus, the contact is considered plastic and the stress on the contact is taken equal to the hardness, i.e., P r ≈ HB. The surfaces of the samples and the counterbody had no waviness, and the contour pressure was determined by the applied load N. Equating the equation approximating the reference curve in the form (3) to the ratio of the contour and actual pressures (7) at the level y = h, the following expression for the absolute convergence of the contacting surfaces is obtained:…”
Section: Contact Stiffness Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were PEO treated in a 10 L tank with the electrolyte having a temperature of 20 ± 1 • C. An aqueous solution of 15 g/L sodium phosphate, 25 g/L calcium acetate, 1 g/L sodium hydroxide and 1 g/L boric acid was selected as the electrolyte composition, as it previously demonstrated the best coating properties [14]. The electrolyte was stirred with an electromagnetic stirrer located under the tank.…”
Section: Peo Coating Formationmentioning
confidence: 99%
“…PEO process can produce biocompatible coatings on zirconium implants due to the porous morphology that imitate the bone surface [12][13][14]. For medical implants, it is crucial that the surface treatment procedure provides coatings of the required quality on devices that typically have complicated shapes, with threaded connections and holes.…”
Section: Introductionmentioning
confidence: 99%